Analysis of Physical Workload and Situational Awareness at the Apron Movement Control (AMC) Unit at Husein Sastranegara International Airport Bandung - Ayuningdias Intan Permatadevi; Walid Jumlad (CV. Rayyan Dwi Bharata, 2023)
Efforts to develop human resources in line with the company's vision and mission are not an easy job, companies are required to be able to prepare a workforce that is able to carry out tasks in work effectively and efficiently. Obstacles that often occur in a company in efforts to develop human resources are high physical workload or workload and lack of situational awareness. This research uses a type of research with a qualitative descriptive method. To be able to get answers from the research, the researcher made a research design design. Qualitative research is research that is used to investigate, find, describe, and explain the quality of influences that cannot be explained, measured or described through a quantitative approach. The results of the study show that the physical workload of the AMC unit at Husein Sastranegara Airport in Bandung is very high due to the very wide coverage of the supervisory area, as well as the great responsibility in supervising and controlling all movements on the air side, with a large number of personnel. experienced a shortage of officers/executors as field workers, where the AMC unit only had 2 officers/executors, therefore with this great responsibility the workload on the AMC unit was also very high. Regarding the condition and form, the level of Situational awareness possessed by AMC officers is already at level 3, because officers can function themselves in the right conditions and at the right time in the surrounding environment in an effective way